Candidozyma auris Colonization and Infection in Intensive Care Units: From Colonization to Candidemia and Clinical Outcomes—A Comprehensive Review - Georgia Dimopoulou; Michael Papadoulakis; Ilias Premetis; Klairi Papachristou; Eleni E. Magira (Journal of Fungi, 2026)
Background: Candidozyma auris (C. auris) is an emerging multidrug-resistant yeast that has become an important cause of healthcare-associated outbreaks, particularly in intensive care units (ICUs). Colonization frequently precedes invasive infection, yet the epidemiology, progression to candidemia, and mortality among critically ill patients remain incompletely characterized. Methods: We conducted a narrative review of published studies evaluating C. auris colonization and infection in ICU populations. Studies reporting colonization rates, progression to invasive infection, and mortality were synthesized. Descriptive pooled proportions were calculated from aggregated data across eligible observational studies. Results: Colonization rates varied widely according to local epidemiology, ranging from 0.2 to 0.4% in routine surveillance studies to over 50% during outbreaks. Across 17 observational studies including 1879 colonized ICU patients, 616 developed invasive infection, yielding a descriptive pooled incidence of 32.8% (95% CI, 30.7–34.9%), predominantly candidemia. The median interval from ICU admission to candidemia was 25.8 days. Among 13 studies including 1354 colonized and/or infected ICU patients, the descriptive pooled 30-day in-hospital mortality was 36.4% (95% CI, 33.8–39.0%). In 12 studies comprising 396 patients with C. auris candidemia, the descriptive pooled 30-day mortality was 45.9% (95% CI, 41.0–50.8%), significantly higher than that observed in mixed colonized/infected ICU populations. Conclusions: C. auris represents a major threat in ICUs because of its ability to establish persistent colonization, progress to invasive candidemia, and cause high mortality among critically ill patients. Early identification of colonized patients, rigorous infection prevention measures, and prompt antifungal management are essential to reduce transmission and improve clinical outcomes.